KEMITRAAN TRIPLE HELIX DALAM PROGRAM PEMAGANGAN KE JEPANG DI PROVINSI JAWA TIMUR - Rizal Hermansyah; Sasmita Jati Utama; M. Husni Tamrin (Aplikasi Administrasi: Media Analisa Masalah Administrasi, 2019)
The study analyzes Triple Helix Partnership in the Japan Internship Program in East Java Manpower and Transmigration Office. There are three actors in apprenticeship programs to Japan, namely academics, business and government. This study aims to describe and analyze who the actors are and how their respective roles in the Triple Helix partnership. The theory uses Widya Fitriana (2015) which states that each actor has their respective roles such as government actors who have the role as regulators, investors, facilitators and advocacy. Business actors have the creative role of entrepreneurship, technology, products, and the driving force of innovation, driving the development of other industrial sectors, contributing to the development of resources. Academic actors have the role of producing research and scientific research, diffusion technology, participating in participatory planning processes and public decision making, providing expert consultation, creating business incubators. It uses descriptive qualitative method. Data collection techniques are obtained through interview, observation, and documentation. The results indicate that government and academy actors have not performed several roles in the apprenticeship program to Japan.